Public Debt Management in Emerging Market Economies : Has This Time Been Different? - Anderson, Phillip R. D. (2012)
Despite the scale of the global financial crisis, to date it has not resulted in a sovereign debt crisis among emerging market countries. Two significant factors in this outcome are the improved macroeconomic management and public debt management in these countries over the past decade. This paper reviews the improvements in macroeconomic fundamentals and the composition of public debt portfolios in emerging market countries prior to the crisis and concludes that the policies and strategies pursued by governments provided them with a buffer when the crisis hit. Nevertheless, with the international capital markets effectively closed for over three months and domestic borrowing in many cases impacted by extreme risk aversion, government debt managers were required to adapt their strategies to rapidly changing circumstances. The paper reviews the impact of the crisis and the responses of debt managers to the drying up of international capital, decreased liquidity in markets, and sharply increased term premia. Three categories of response are identified: (i) funding from other sources to reduce pressure on market borrowing; (ii) adapting funding programs to changes in demand in the different types of securities; and (iii) implementing liability management operations to support the market. Most governments were willing to accept temporarily greater risk in their portfolios, often reversing long established strategies, at a time when financial markets were under stress. These actions contributed to the measures taken by governments to stabilize markets and prevent economies from stalling. Looking to the future, government debt managers will need to consider how they can increase the resilience of public debt portfolios for the uncertain times that lie ahead.